How Do First-Mover Firms Use Entrepreneurial Behaviour To Expand Their Market-Share? - Preciado Carpio, Jorge (2012)
The purpose of this case study is to analyse the relationship between the internal Entrepreneurial Behaviour in a First-Mover Firm in Mexico and its leadership position in the market place. Usually large established firms are more effective at orchestrating resources to identify opportunities for the creation of competitive advantages and wealth creation. Therefore, an extensive analysis is required to determine which entrepreneurial approaches are important for a FM. Moreover, to link these entrepreneurial approaches to a real case study is determinant. Consequently, elemental conditions that a firm should consider when aligning targets and goals with an Entrepreneurial orientation are explained. This case study attempts to provide a basis for future research into the relationship between entrepreneurial approaches and First-Mover firm wealth creation.